التدخل في الشؤون الداخلية للدول (( دراسة قانونية في إطار مبادئ القانون الدولي والعلاقات الدولية )) (Comprehensive Journal of Science, 2025)
The concept of external intervention is a complex subject that addresses multiple legal, political, and ethical aspects. It is particularly important in the context of international organizations such as the United Nations. This concept addresses how other states intervene, often under the pretext of protecting human rights or disturbing international peace and security. External intervention is a diverse subject in its outlook, depending on the country's legal status and the prevailing international position. The principle of sovereignty remains the foundation, except in cases that require international intervention to protect human rights.